2020
DOI: 10.1021/acsmedchemlett.0c00586
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Metabolism of BTN3A1 Ligands: Studies on Modifications of the Allylic Alcohol

Abstract: (E)-4-Hydroxy-3-methyl-but-2-enyl diphosphate (HMBPP) and its phosphonate analogs are potent phosphoantigens. HMBPP contains an (E)-allylic alcohol which interacts with the molecular target BTN3A1 giving an antigenic signal to activate Vγ9Vδ2 T cells. As probes of BTN3A1 function, we prepared prodrug derivatives of the HMBPP analog C-HMBP that lack the (E)-allylic alcohol or have modified it to an aldehyde or aldoxime and evaluated their biological activity. Removal of the alcohol completely abrogates phosphoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 45 publications
1
5
1
Order By: Relevance
“…This is because in cells treated with acetate 13 , a significant m / z of 712.2507 consistent with [M+307-H] − of deacetylated 13 was found, indicative of glutathione conjugation. Similar glutathione conjugates were also observed in our prior study on pAg aldehydes . In the present study, glutathione conjugates were not observed with other dienes such as 9 , 21 , or 24 .…”
supporting
confidence: 92%
See 4 more Smart Citations
“…This is because in cells treated with acetate 13 , a significant m / z of 712.2507 consistent with [M+307-H] − of deacetylated 13 was found, indicative of glutathione conjugation. Similar glutathione conjugates were also observed in our prior study on pAg aldehydes . In the present study, glutathione conjugates were not observed with other dienes such as 9 , 21 , or 24 .…”
supporting
confidence: 92%
“…Similar glutathione conjugates were also observed in our prior study on pAg aldehydes. 25 In the present study, glutathione conjugates were not observed with other dienes such as 9, 21, or 24. Therefore, the presence of the oxygen on the diene scaffold presents a metabolism barrier to the activity of compounds such as 13.…”
contrasting
confidence: 50%
See 3 more Smart Citations